Advertising and Profitability - Sherman, Roger; Tollison, Robert (The Review of Economics and Statistics, 1971)
unemployment rates quoted in table 1; however, a fuller statement is available on request from the author. The United Kingdom figures for 1960 onward are based on a letter to the author (dated 28/1/71) revising [7]. For earlier years the official statistics have been raised by a percentage based on the revised BLS information. Percentage adjustments have also been made to the French (Institut National de la Statistique et des Etudes Economiques) and German (registration series from the ILO Yearbook of Labour Statistics) figures in similar fashion, except that the 1958 German figure was supplied by the BLS. The Swedish figures for 1953-1961 come from [3]. The Italian figures for 1954-1958 are based on the irregular ISTAT surveys adjusted for seasonality and for comparability with United States definitions (the latter on an absolute basis) on the basis of experience since 1959. The 1953 figure, for reasons described in the supplementary statement, is the average for 1954-1956. The Australian unemployment rates for 1964 and 1965 are those of the Commonwealth Statistician, while those for 1958-1963 are based on an upward percentage adjustment of the Department of Labour and National Service's registration series. The Belgian figures throughout are based on the percentage reductions indicated by [10] and [11]. The Dutch rates are those contained in the ILO Yearbook, since [10] and [11] indicated slight adjustments in conflicting directions.